2021
DOI: 10.3390/ani11102840
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antiapoptotic Effects of a Turraea fischeri Leaf Extract on Cryopreserved Goat Sperm

Abstract: This study evaluated the efficacy of Turraea fischeri leaf extract for maintaining the viability of cryopreserved goat sperm. Ejaculated semen was collected from 5 mature Baladi bucks (50–60 kg, 2–4 years of age) and those samples with mass motility ≥ 70% and sperm concentration ≥ 2.5 × 109/mL were selected, pooled, and divided into 4 aliquots. Each aliquot was diluted in Tris-citric-soybean lecithin extender containing a different concentration of T. fischeri leaf extract (0, 125, 250, or 375 µg/mL). Treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…Here, the supplementation of ram semen extenders with BBE enhanced the proportion of viable sperm and reduced that of apoptotic sperm, suggesting that BBE has anti-programmed death properties. This is in agreement with the results obtained for small ruminants using medicinal plants for semen cryopreservation [ 38 , 66 , 67 ]. Treatment of high-fat diet-induced obese male rats with bee bread upregulated testicular antioxidant enzymes and downregulated apoptosis genes [ 68 , 69 ].…”
Section: Discussionsupporting
confidence: 92%
“…Here, the supplementation of ram semen extenders with BBE enhanced the proportion of viable sperm and reduced that of apoptotic sperm, suggesting that BBE has anti-programmed death properties. This is in agreement with the results obtained for small ruminants using medicinal plants for semen cryopreservation [ 38 , 66 , 67 ]. Treatment of high-fat diet-induced obese male rats with bee bread upregulated testicular antioxidant enzymes and downregulated apoptosis genes [ 68 , 69 ].…”
Section: Discussionsupporting
confidence: 92%
“…To maintain sperm quality during the cryopreservation process, it is important to balance the production of ROS and its scavenging. A major strategy for enhancing goat sperm’s resistance to oxidative stress during cryopreservation is the supplementation of exogenous antioxidants in the freezing medium, such as glutathione [ 19 ], green synthesized anionic cupric oxide nanoparticles [ 20 ], Lycium barbarum and Laminaria japonica polysaccharides [ 21 ], turraea fischeri leaf extract [ 22 ], resveratrol and taurine [ 23 ], vitamin E and amino acids [ 24 ], trehalose [ 25 ], myo-inositol and melatonin [ 26 ]. However, most of the exogenous antioxidants are unstable due to oxidation; hence, they lose their anti-oxidative capacity.…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in neutralizing and suppressing free radical production via interacting with α-tocopherol and eventually declining lipid peroxidation ( 24 ). In other studies, quercetin enhanced TAC contents that improved semen parameters in humans and goats ( 79 , 80 ). Barranco et al ( 81 ) revealed that high contents of TAC in boar seminal plasma were related to sperm survival and fertility and can be used as a marker for predicting fertility.…”
Section: Discussionmentioning
confidence: 64%